MANAJEMEN RISIKO BISNIS UMKM DI KOTA SURAKARTA - Wajdi, M. Farid; Setyawan, Anton Agus; Syamsudin, Syamsudin; Isa, Muzakar (Universitas Muhammadiyah Surakarta, 2012)
The purpose of this study is to analyze the business risks that arise from a disaster thatbegins with SMEs understanding of business risk from disasters in Surakarta. Furthermore, is toanalyzed risk perception the in Surakarta SMEs, which most likely can happen and the impact ontheir businesses. In addition, this study also identifies the problems and opportunities of riskmanagement in SMEs at Surakarta. The population of this study was SMEs entrepreneurs inSurakarta. Data collection was done by two methods: survey and in-depth interviews. Descriptivestatistical methods were used in this study were the frequency and value of cross-tab analysis toclassify data. Research results indicate that (1) presence Indonesian SMEs in general and inSurakarta in particular is essential for economic growth. (2) The management of SMEs can not beseparated on the threat of business risks that may arise from time to time. (3) Risk management is not only a SMEs responsibility solely, but also the responsibility of the Government and relevant institutions risk management business (Banking and Insurance). (4)The impact of the disaster,which is one business risk for SMEs can be transferred to the insurance as an institution that can help guarantee against losses caused by the disaster.